PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 025 SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Asrida Harahap; Zulkifli Zulkifli; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : this Research have go to to to level it result study IPA with to use it studying model implement inkuiri to student V SDN class 025 Sekeladi.that to be executed to month March until with April 2015. research Subjek is student V SDN class 025 Soil Sekeladi White Kabupaten Rokan Hilir who add 21 people this Research is the class action research that consist from two cycles, that is four times meeting and two times repeating of daily. data Instrument collection in this research is activity sheet and activity sheet also studying result Activity of teacher in studying process to cycle one first meeting is 58,33% with enough category to meeting second 66,66% with good category two Cycle to meeting first to level become 75% with good category and second meeting to level become 83,33% with category very good.. analysis Result data ctivity of student to cycle one first meeting that is 54,16%, with enough category. second meeting to level become 62,50% with category good. to cycle two first meeting to level become 70,83% with good category and to meeting second to level become 83,33% with category very good. Average result study student to undergo leveling. Average result study to base skor is 61,90, to cycle one with value average 70,71to undergo as big as leveling 14,23% , to cycle two to level become 79,04, to undergo leveling from base skor as big as 27,69%. research result To be based mentioned so can to be concluded that Studying Model Implement Inkuiri can to level it result study class student IPA V SDN 025 Soil Sekeladi White Kabupaten Rokan Hilir.Key Word : Studying Model Inkuiri . Result study IPA